PENGARUH KEMAMPUAN BELAJAR DAN BUDAYA BELAJAR TERHADAP KINERJA KARYAWAN PT MASAJI TATANAN KONTAINER INDONESIA JAKARTA - Agustine Citra Devi Oyan; Tatag Herbayu (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The analyze the influence of learning agility and learning culture on employee performance PT. Masaji Indonesian Container Management Jakarta. This research is included in the category of causal associative research using a quantitative approach. The population in this study were all employees of PT. Masaji Indonesian Container Management Jakarta. By using the Isaac and Michael formula to determine the number of samples based on the error rate. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the learning agility and learning culture have a positive and significant effect on the organizational performance of PT. Masaji Indonesian Container Management Jakarta.